Effect of discrete heating-cooling on magneto-thermal-hybrid nanofluidic convection in cylindrical system. (15th January 2023) - Chatterjee, Deep; Biswas, Nirmalendu; Manna, Nirmal K.; Sarkar, Sandip
Abstract: In search of efficient energy utilization and superior thermal performance, the present study is aimed at understanding the positional effect of discrete heaters and coolers on a cylindrical thermal system. This system undergoes a magneto-thermal convective process using Cu-Al2 O3 H2 O hybrid nanofluid. Four options are investigated by altering the position of four heater and cooler segments mounted centrally on the wall of four quadrants of the cylinder. The equations of motion and energy are solved in nondimensionalized form by employing the finite element technique. The effects of operating parameters on the thermal transport are investigated systematically for a fixed nanoparticle volume fraction ( φ ) and a range of the Rayleigh number (signifying the buoyant forces), Hartmann number (signifying the magnetic field strength), and the magnetic field inclination ( γ ). The study shows that heat transfer, as well as entropy production, is markedly influenced by the heater-cooler positions and flow-controlling parameters. Among all the studied configurations, two cases show the optimum value of the Nusselt number. The cross heater-cooler arrangement affirms as the most effective heating-cooling option to obtain enhanced heat transfer. Higher heat transfer corresponds to greater entropy production. Higher magnetic field intensity dampens the heat transfer rate and thermodynamic irreversibility. The innovative identification of superior cross-wise heating-cooling over the usual side-side or bottom-top heating-cooling is the major outcome of this study. The experimental hybrid nanofluid properties are considered for this study. Graphical abstract: Image, graphical abstract